Prevalence of various forms of peripheral neuropathy in patients with systemic connective tissue diseases: a clinical and electrophysiological study - Djurić, Vanja; Stamenković, Bojana; Petković, Ivan; Djurić, Luka (Vojnosanitetski pregled, 2023)
Background/Aim. Peripheral neuropathy (PN) in systemic connective tissue diseases (SCTDs) represents the apparent disease complications or initial manifestations of clinically undiagnosed conditions. The aim of the study was to identify neuropathies (Ns) and their prevalence, point out the diagnostic significance of some electrophysiological (EP) parameters in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and systemic sclerosis (SSc), and establish their association with disease activity (DA) and disease duration (DDu). Methods. A prospective study was conducted at the Rheumatology Clinic of the Institute for Treatment and Rehabilitation “Niška Banja” over a three-year period. The study included 157 patients in total, of whom 61 had RA, 40 had SLE, and 56 had SSc. The following parameters were analyzed: age, gender, DDu, course of the disease, and DA index. Moreover, clinical, rheumatological, and neurological examinations, as well as neurology tests, nerve conduction studies (NCS), and laboratory analyses, were also conducted. Results. In the studied population, we were able to identify various forms of Ns (in 28.7% of patients) by NCS. In all three groups, the most prevalent type of Ns was axonal (23.6%), sensorimotor (18.5%), and polyneuropathy (23.6%). There was a significant association between DA and the occurrence of Ns (p < 0.001) in the total population. The most important EP parameter was the sensory nerve action potential amplitude of nervus peroneus superficialis [in 70 (44.6%) patients] and nervus suralis [in 35 (22.3%) patients], and compound muscle action potential amplitude of nervus peroneus [in 32 (20.4%) patients]. DDu in all three groups was longer in the population of patients with Ns. Conclusion. Ns are most common in patients with longer DDu and higher DA. The EP method is important in detecting Ns, especially in the early detection of subclinical forms of Ns and the prevention of disease complications.
Keywords: arthritis, rheumatoid; autoimmune diseases; connective tissue; diagnosis; lupus erythematosus, systemic; peripheral nervous system diseases; scleroderma, systemic